Masculinities, Media and the Rugby Mind: An Analysis of Stakeholder Views on the Relationship Between Rugby Union, the Media, Masculine-Influenced Views on Injury, and Concussion. (June 2022) - Parry, Keith; White, Adam J.; Cleland, Jamie; Hardwicke, Jack; Batten, John; Piggin, Joe; Howarth, Nathan
Rugby union, alongside other collision and contact sports, faces ever mounting pressure from increased recognition of concussive injuries and the risks they present to athletes, both in the short-term and long-term. Here, the media is a central component of increasing pressure for cultural change. This research analysed data from 524 self-selected survey respondents to examine rugby union fans' and stakeholders' perceptions of media portrayal of concussion and how it might influence their own perceptions. We found evidence of a complex and heterogenous relationship between perceptions of masculinity, views and attitudes toward mass media, and degree of involvement in rugby union. Specifically, partisans of the sport generally saw mass media as hostile, with coverage biased against rugby, allowing them to manufacture doubt regarding risk information, as well as maintaining involvement in the sport. We conclude that critical commentaries from the media have the ability to challenge masculinities around concussion.